The Effect of Applying Life skills training program on Substance Abuse Behaviors of Male Preparatory Schools Students in Alexandria - harfosh, mohammed (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2020)
Abstract:Background: Prevention and early intervention of substance abuse represent the most promising and appropriate ways to maximize adolescent's health and minimize the negative and serious consequences of such pervasive problem. Therefore, effective prevention strategies are critically important in community efforts to combat such problem. Objective: Identify the impact of applying preventive interventions on substance abuse behaviors of male preparatory schools students in Alexandria. Settings: The study was carried out at four governmental male preparatory schools representing two educational zones of Alexandria Governorate affiliated to the Ministry of Education. El-Montazah (Elbactoshy and El-Shaheed Hanafy Mahmoud), East (Esmael Elkabany and Mohamed Hafez). Subjects: a) All students in the first and second grades in the previously selected schools were screened by using Alcohol, Smoking and Substance Involvement Screening Test (ASSIST), they were 3493 students. b) Thirty students from those having mild or moderate substance abuse related risk were randomly selected from each school (total number was 120 students). Tools: Two tools were used for data collection. The first tool was Students' socio-demographic and health profile structured interview schedule. The second tool was Alcohol, Smoking and Substance Involvement Screening Test (ASSIST). The study had four phases. The first was the assessment and preparatory phase where tool (II) was used to assess students' substance abuse behaviors, the second was the development phase while the third was the implantation phase and finally the fourth phase was the evaluation phase during which tool (II) was reused for immediate and 3 month and 6 month follow up evaluation. Results: results of the study  implies that the total ASSIST mean score for smoking/substance use among study group students was significantly decreased from 40.17± 15.54 before the program implementation phase to 7.20 ± 12.75 immediately after the program implementation. Further reductions were reported in each of 3 and 6 months follow up assessment (3.92± 10.28 and 2.21± 1.39 respectively). Conclusion: The study concluded that the preventive interventions based on life skills training program were the most promising strategies for combating substance use among adolescents. Recommendations: Evidence based substance use preventive interventions like life skills training program must be rooted in school curriculum. Keywords: Substance abuse, Adolescents, life skills, prevention.